2013
DOI: 10.1111/trf.12530
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus seroprevalence and molecular study among blood donors in China

Abstract: Qualified donations after routine blood donor screening still carry potential risk for transmitting HEV. HEV antigen screening could be one measure to reduce the risk of HEV transmission by blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
43
3
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 34 publications
(90 reference statements)
15
43
3
4
Order By: Relevance
“…Meanwhile, differences between IgG prevalence were observed across provinces in China. Similar to other studies, our findings showed a higher anti-HEV IgG prevalence among provinces located in southern China which may suggest that geographical region is an important factor for HEV infection[29]. In Liaoning province, IgM prevalence was found to be higher than that of other regions (p = 0.311), since one of the studies performed in Liaoning collected samples from a garrison army in which 2 soldiers were diagnosed as hepatitis E[21].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Meanwhile, differences between IgG prevalence were observed across provinces in China. Similar to other studies, our findings showed a higher anti-HEV IgG prevalence among provinces located in southern China which may suggest that geographical region is an important factor for HEV infection[29]. In Liaoning province, IgM prevalence was found to be higher than that of other regions (p = 0.311), since one of the studies performed in Liaoning collected samples from a garrison army in which 2 soldiers were diagnosed as hepatitis E[21].…”
Section: Discussionsupporting
confidence: 88%
“…Among the 14 selected articles, 3 articles reported the genotypes of HEV [22,24,29]. HEV RNA was sequenced directly on both strands with specific primers and then the sequence was aligned with the sequence of the standard strains of the four HEV genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…A separate epidemiological strand has associated HEV infection with blood transfusion in a number of countries, 1 and a recent China based study has reported on Sporadic HEV infection in China 7 discovering HEV RNA in blood donors. 24 However in the current patient cohort only one individual reported having a blood transfusion in the 50 days prior to admission for HEV infection. Therefore, although no direct evidence was found to link HEV infection to blood donation in this study, the risk of blood based transmission should not be ignored.…”
Section: Discussionmentioning
confidence: 98%
“…HEV RNA has been detected in asymptomatic blood donors from the UK, Japan, Germany, Saudi Arabia, Scotland, Spain, Austria, the Netherlands and China (15,180,185,187,189,190,225,255,260). Moreover, cases of TT-HEV have been reported in the UK, Japan, France and Germany (17,190,260,261).…”
Section: Introductionmentioning
confidence: 92%
“…The Wantai HEV IgG ELISA manufactured by Beijing Wantai Biological Pharmaceutical Enterprise Co., Ltd is considered to be the most specific and sensitive assay available at present (184). This commercial assay has also been widely used for HEV seroprevalence studies (162,178,184,225), and is therefore preferred for the current study to allow a comparison with these other studies.…”
Section: Hev Igg Assaysmentioning
confidence: 99%